Hierarchically intelligent machines - Saridis, George N., 1931- (World Scientific, 2001)
This work presents the result of 30 years' work on the original material related to "thinking machines", a subject initiated by the author and his colleagues. It is based on the ability of the computer to represent the hierarchical procedure of task conception and execution found in human beings. It is arranged in three levels representing the structure of organizational systems: organization, co-ordination and execution. The volume can serve as a guide to modern intelligent robots